2018
DOI: 10.1080/07357907.2018.1499934
|View full text |Cite
|
Sign up to set email alerts
|

Differential Claudin 3 and EGFR Expression Predicts BRCA1 Mutation in Triple-Negative Breast Cancer

Abstract: BRCA-1 mutation-associated triple-negative breast cancer (TNBC) has been hypothesized to exhibit a phenotype that is distinct from non-mutation carriers. We have analyzed immunohistochemically detected cytokeratins 5 and 14, epidermal growth factor receptor (EGFR), claudin (CLDN) 3, 4, and 7, and E-cadherin in 57 TNBC (32 BRCA1 and 8 BRCA2 tumors, 17 WT tumors). Positive staining of CLDN3 and negative EGFR expression in TNBC are associated with a BRCA1 mutation. EGFR and CLDN3 expression was able to predict th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…The multivariate regression model by Danzinger et al (2018) revealed that claudin-3 was 22 times more likely to be observed in BRCA1-mutated triple negative breast cancer (TNBC) in comparison to BRCA2 and non-mutated TNBC. What is more, expression of claudin-3 was an independent marker of BRCA1 mutation status in TNBC in a univariate analysis [55]. Van Heerma Voss et al (2014) described overexpression of claudin-3, -6 and -7 in BRCA1-mutated tumor tissue in comparison to adjacent healthy tissue.…”
Section: Claudinsmentioning
confidence: 96%
See 2 more Smart Citations
“…The multivariate regression model by Danzinger et al (2018) revealed that claudin-3 was 22 times more likely to be observed in BRCA1-mutated triple negative breast cancer (TNBC) in comparison to BRCA2 and non-mutated TNBC. What is more, expression of claudin-3 was an independent marker of BRCA1 mutation status in TNBC in a univariate analysis [55]. Van Heerma Voss et al (2014) described overexpression of claudin-3, -6 and -7 in BRCA1-mutated tumor tissue in comparison to adjacent healthy tissue.…”
Section: Claudinsmentioning
confidence: 96%
“…Mavaddat et al (2010) also highlighted a potentially important role of ER, CK5/6 and CK14 in prediction of BRCA1-mutated cases [96]. On the other hand, Danzinger et al (2018) found no significant correlation between expression levels of CK5 and CK14 among the BRCA1, BRCA2 and non-mutated group in TNBC. In the performed ROC analysis they found that claudin-3 and EGFR expression levels were able to predict BRCA1 mutation status in TNBC with fairly high sensitivity and specificity (area under curve 0.802, p < 0.001) [55].…”
Section: Sets Of Markers Useful In Selecting Probable Brca-1 Mutationmentioning
confidence: 99%
See 1 more Smart Citation
“…Claudin-7 expression correlated with shorter overall survival in gastric cancer patients, while the overall survival was increased in patients with claudin-18 expression. Recently, claudin-3 and -7 are also considered as novel prognostic factors in triple-negative breast cancer (TNBC) through its aberrant immunohistochemical expressions [107]. Claudin-3 cytoplasmic expression is an indicator of poor survival in triple-negative breast cancer.…”
Section: Claudins In Prognosismentioning
confidence: 99%
“…In an interesting article by Danzinger et al, the importance of claudin-3 in triple-negative breast cancer (TNBC) was documented. It was reported that claudin-3 expression was correlated with a Breast cancer type 1 (BRCA1) mutation [107]. This could help in guiding the decision for BRCA testing for triple-negative breast cancer (TNBC).…”
Section: Claudins In Prognosismentioning
confidence: 99%